Mechanistic insights on the Dicer-independent AGO2-mediated processing of AgoshRNAs - Liu, Ying Poi (RNA Biol, 2015)
Short hairpin RNAs (shRNAs) are widely used for gene knockdown by inducing the RNA interference (RNAi) mechanism, both for research and therapeutic purposes. The shRNA precursor is processed by the RNase III-like enzyme Dicer into biologically active small interfering RNA (siRNA). This effector molecule subsequently targets a complementary mRNA for destruction via the Argonaute 2 (AGO2) complex. The cellular role of Dicer concerns the processing of pre-miRNAs into mature microRNA (miRNA). Recently, a non-canonical pathway was reported for the biogenesis of miR-451, which bypasses Dicer and is processed instead by the slicer activity of AGO2, followed by the regular AGO2-mediated mRNA targeting step. Interestingly, shRNA designs that are characterized by a relatively short basepaired stem also bypass Dicer to be processed by AGO2. We named this design AgoshRNA as these molecules depend on AGO2 both for processing and silencing activity. In this study, we investigated diverse mechanistic aspects of this new class of AgoshRNA molecules. We probed the requirements for AGO2-mediated processing of AgoshRNAs by modification of the proposed cleavage site in the hairpin. We demonstrate by deep sequencing that AGO2-processed AgoshRNAs produce RNA effector molecules with more discrete ends than the products of the regular shRNA design. Furthermore, we tested whether trimming and tailing occurs upon AGO2-mediated processing of AgoshRNAs, similar to what has been described for miR-451. Finally, we tested the prediction that AgoshRNA activity, unlike that of regular shRNAs, is maintained in Dicer-deficient cell types. These mechanistic insights could aid in the design of optimised AgoshRNA tools and therapeutics.